Сivic orientation of the individual as a "second order" system property - Liubov, Volodymyr Fushtei , Kostiv (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the idea of civic orientation of the individual as a second ordersystem. The cosmopolitan, patriotic, nationalistic and chauvinistic kinds of civic orientation ofthe individual are highlighted. The relationship between orientation in the system of civicculture and other cultures of a person is revealed. The methods of study of civic orientation ofthe individual are designed. The results of civic orientation of adolescents are analyzed. Key words: orientation of the individual, civic orientation of a person, types of civicorientation, research methodology of the individual civic orientation, the results of the civilorientation of older teens.